Pemilihan Supplier Bahan Baku Batu Menggunakan Metode Analytical Hierarchy Process (AHP) Dengan Software Expert Choice 11 Pada CV Al-Mariah (Lembaga Pengembangan Kinerja Dosen, 2025)
Selecting the right supplier is a crucial factor in supporting the smooth operation of a company, especially in the natural stone handicraft industry. CV Al-Mariah, located in West Bandung Regency, faces challenges in determining the best raw stone material supplier due to issues such as uncertain supply quantities and delayed deliveries, which disrupt production processes. This study aims to analyze and determine the best supplier using the Analytical Hierarchy Process (AHP) method, processed with Expert choice 11 software. Data were collected through questionnaires distributed to parties directly involved in the raw material procurement process. The results show that among the three supplier alternatives analyzed, Supplier B obtained the highest weight of 0.380, followed by Supplier A with 0.352, and Supplier C with 0.268. Therefore, Supplier B is recommended as the top choice to support the operations of CV Al-Mariah. The AHP method has proven effective in assisting complex decision-making processes by systematically considering multiple criteria.